Case Report: Tissue Origin Identification for Cancer of Unknown Primary: Gene Expression Profiling Approach - Pu, Xingxiang; Yang, Sa; Xu, Yan; Chen, Bolin; Wang, Qianzhi; Gong, Qian; Wu, Lin (Frontiers in Oncology, 2021)
The treatment of cancer of unknown primary (CUP) is a huge challenge for clinicians. Gene expression profiling can help identify the tissue origin of tumors by detecting the expression levels of specific genes in tumor tissues. Herein, we report four CUP cases. All of them have been successfully identified with the corresponding primary tumor sites through gene expression profiling analysis. Then all patients received accurate treatment, providing reference to guide therapeutic decisions to treat CUP tumors in the future.